2016
DOI: 10.1589/jpts.28.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional limitations due to foot involvement in spondyloarthritis

Abstract: [Purpose] Spondyloarthritis is a major inflammatory disease followed-up in the rheumatology clinics, foot involvement in spodyloarthritis is common. The functional states of patients with spondyloarthritis are usually evaluated globally. The aim of this study was to assess the foot involvement-related functional limitations in patients with spondyloarthritis. [Subjects and Methods] Patients with ankylosing spondylitis and psoriatic arthritis with foot pain more than 4 weeks who underwent anteroposterior and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…This study showed that the disease duration and CRP levels were not correlated with self-reported foot pain and function, which is consistent with results from a previous study conducted in people with spondyloarthritis [ 63 ]. On the other hand, gait spatiotemporal parameters, especially gait speed, were strongly correlated with these clinical outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that the disease duration and CRP levels were not correlated with self-reported foot pain and function, which is consistent with results from a previous study conducted in people with spondyloarthritis [ 63 ]. On the other hand, gait spatiotemporal parameters, especially gait speed, were strongly correlated with these clinical outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Significant functional and emotional challenges resulting from symptoms, side effects, and complications may also include anxiety, depression, mood disorders, and decreased health-related quality of life [ 24 – 27 ], which further increase service use costs. In another study, Ozaras et al [ 28 ] observed that in patients with ankylosing spondylitis and psoriatic arthritis, disease activity (self-reported pain and symptoms) was associated with greater physical limitation. Given the direct relationships observed between disease activity, comorbidities, and limitations [ 17 , 28 31 ], the provision of optimal care to individuals with arthritis and joint pain is critical.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Ozaras et al [ 28 ] observed that in patients with ankylosing spondylitis and psoriatic arthritis, disease activity (self-reported pain and symptoms) was associated with greater physical limitation. Given the direct relationships observed between disease activity, comorbidities, and limitations [ 17 , 28 31 ], the provision of optimal care to individuals with arthritis and joint pain is critical. This ultimately results in control of disease and slows the progression of related complications such as functional, activity, and sensory limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Data from India indicate that involvement of the mid-foot is common and severe (17). Likewise, tarsal bone ankylosis was seen in patients with oligoarticular juvenile rheumatoid arthritis and back pain from India (51) and Turkey (52,53).…”
Section: Foot Involvement and Tarsitismentioning
confidence: 99%